The effect of on buyers’ decision the CV Sinarayu Werasari Majalengka - Royani, Solihin; Burhan, Aceng; Fhatonah, Silvi Siti (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
The purpose of conducting this research is to collect information that will be used to analyze the effect of pricing on purchasing decisions for building equipment at the CV Sinarayu Werasari, Majalengka Regency. And is expected to assist the company in solving the problems faced in accordance with the topic taken by the author, by analyzing, especially information and data regarding the effect of pricing on purchasing decisions. This research was conducted at the CV Sinarayu Werasari Majalengka, Regency., and hypothesis testing using t test. There is an influence between pricing on purchasing decisions because the t-valuecount of 14,618 is greater than the t-table, namely 0,305 for the two-party test with a significant level of 0.05 at dk = 94, then Ha is accepted, thus the author can draw the conclusion that the level of determination price can support purchasing decisions